MEDB-06. Spatial transcriptomic analysis of Sonic Hedgehog Medulloblastoma identifies that loss of heterogeneity and induced differentiation underlies the response to CDK4/6 inhibition. (3rd June 2022) - Vo, Tuan; Balderson, Brad; Jones, Kahli; Crawford, Joanna; Millar, Amanda; Tolson, Elissa; Ruitenberg, Marc; Robertson, Thomas; Bhuva, Dharmesh; Davis, Melissa; Wainwright, Brandon; Nguyen, Quan; et al.
Abstract: Medulloblastoma (MB) is a malignant tumour of the cerebellum which can be classified into four major subgroups on the basis of gene expression and genomic features. Single cell transcriptome studies have defined the cellular states underlying each MB subgroup, however the spatial organisation of these diverse cell states and how this impacts response to therapy remains to be determined. Here, we used spatially resolved transcriptomics to define the cellular diversity within a sonic hedgehog (SHH) patient-derived model of MB and identify how cells specific to a transcriptional state or spatial location are pivotal in responses to treatment with the CDK4/6 inhibitor, Palbociclib. We distinguish neoplastic and non-neoplastic cells within tumours and from the surrounding cerebellar tissue, further refining pathological annotation. We identify a regional response to Palbociclib, with reduced proliferation and induced neuronal differentiation in the majority of the tumours. Additionally, we resolve in cellular resolution a distinct tumour "interface" where the tumour contacts neighbouring mouse brain consisting of abundant astrocytes and microglia and continues to proliferate despite Palbociclib treatment. Our data highlight the power of this approach to characterise the response of a tumour to targeted therapy and provide further insights into the molecular and cellular basis underlying the response and resistance to CDK4/6 inhibitors in SHH MB